Diseño de un modelo de cobranza para disminuir la cartera vencida en la Corporación Nacional de Electricidad (CNEL) sucursal Calceta - Intriago Salas, Gema Estefanía (2014)
This research entitled "Designing a collection model to reduce non-performing loans for the National Power Corporation (CNEL) “Calceta branch" document that will respond to all the concerns of the financial area, indicating the steps to recover loans. The synthesis of the research work contains: In the first chapter planning and formulation of the problem, justification and delimitation of the problem, which is studied in the present, and the general and specific objectives to be achieved during research. In the second chapter we have the theoretical framework, which includes the background research. The third chapter is about the same methodological design in which we will determine the mode of research, type of research, population and sample, methods, techniques and tools used throughout the development, the results of surveys to clients, and an interview with Mr. Manager Utility, which has allowed the respective analysis of the hypotheses verification. And finally in the fourth chapter we proposed management model designed for the utility CNEL, the same that contains: Introduction, summary, objective of the proposal, rationale and strategic direction; that will guide the manager for taking decisions in terms of reducing delinquency.